Charles Dicken - เอิร์สกิน-ฮิลล์ ลินดา (Journal of the Faculty of Arts, Silpakorn University, 2020)
To celebrate the 200th anniversary of the birth of Charles Dickens, this article presents an overview of his life and works. It begins with a brief description of London in the early 19th century, and continues to describe Dickens’ early years in Kent and London and the start of his working life. The article outlines Dickens’ literary career, visits to America, and concludes with his final days at Gad’s Hill in Kent.